 # Warm Up Section 3.6B (1). Show that f(x) = 3x + 5 and g(x) =

## Presentation on theme: "Warm Up Section 3.6B (1). Show that f(x) = 3x + 5 and g(x) ="— Presentation transcript:

Warm Up Section 3.6B (1). Show that f(x) = 3x + 5 and g(x) = are inverses. (2). Find the inverse of h(x) = 8 – 3x. (3). Solve: 27 x – 1 < 92x + 3 (4). Is k(x) = 4.6x increasing or decreasing throughout its domain? x – 5 3

Answers to Warm Up Section 3.6B
(1). f(g(x)) g(f(x)) = f( ) = g(3x + 5) = 3( ) = = x – = = x = x x – 5 3 x – 5 3 3x + 5 – 5 3 3x 3

x – 8 -3 (2). h-1(x) = (3). x > -9 (4). Increasing

1. Increasing 2. Decreasing 3. Increasing 4.
3.5b Homework Answers 1. Increasing 2. Decreasing 3. Increasing 4. Decay Domain: all reals Range: y > -3 Asymptote: y = -3 Zeros: between -2 and -1 y-int: (0, -2) Inc: none / Dec: all reals Rate of change: -15/16 End Behavior: L: x → -∞, y → ∞ R: x → ∞, y → -3

Growth Domain: all reals Range: y > 1 Asymptote: y = 1 Zeros: none y-int: (0, 2) Inc: all reals / Dec: none Rate of change: 15/16 End Behavior: L: x → -∞, y → 1 R: x → ∞, y → ∞ 5. 6. decay 7. growth 8. growth 9. decay 10. decay 11. growth

Growth Domain: all reals
Range: y > Asymptote: y = 3 Zeros: none y-int: (0, 3.25) Increasing End Behavior: 12. Decay Domain: all reals Range: y > Asymptote: y = 1 Zeros: none y-int: (0, 5) Decreasing End Behavior: 13.

Decay Domain: all reals
Range: y > Asymptote: y = 2 Zeros: none y-int: (0, 3) Decreasing End Behavior: 14. Growth Domain: all reals Range: y > Asymptote: y = 0 Zeros: none y-int: (0, 3) Increasing End Behavior: 15.

Geometric Sequences and Series
Section 3.6 Standard: MM2A2 f g Essential Question: What are the sums of finite geometric sequences and series? How do geometric sequences relate to exponential functions?

Vocabulary Geometric Sequence: A sequence in which the ratio of any term to the previous term is constant. Common Ratio: The constant ratio between consecutive terms of a geometric sequence, denoted by r. Geometric Series: The expression formed by adding the terms of a geometric sequence.

Investigation 1: Recall: An arithmetic sequence is a sequence in which the difference between two consecutive terms is constant. The constant difference between terms of an arithmetic sequence is denoted d and the explicit formula to find the nth term of a sequence is: an = a1 + d(n – 1).

Identify the next three terms of the arithmetic
sequence, then write the explicit formula for the sequence: , 7, 11, 15, an = 3 + 4(n – 1) or an = 4n – 1 19, 23, 27, . . . Use the formula from example #1 to find the 27th term of the sequence. a27 = 3 + 4(27 – 1) = 107 What is the sum of the first 27 terms of this sequence. Hint: use

In an arithmetic sequence, the terms are found by adding a constant amount to the preceding term. In a geometric sequence, the terms are found by multiplying each term after the first by a constant amount. This constant multiplier is called the common ratio and is denoted r. For each geometric sequence, identify the common ratio, r. 2, 6, 18, 54, 162, . . . 5, 50, 500, 5000, . . . 3, , , , . . . -4, 24, -144, 864, -5184, . . . r = 3 r = 10 r = ½ r = -6

Tell whether the sequences is arithmetic, geometric or neither
Tell whether the sequences is arithmetic, geometric or neither. For arithmetic sequences, give the common difference. For geometric sequences, give the common ratio. 5, 10, 15, 20, 25, …. 1, 1, 2, 3, 5, 8, 13, 21, … 1, -4, 16, -64, 256, … , 256, 128, 64, 32, … arithmetic; d = 5 neither geometric; r = -4 geometric; r = ½

Check for Understanding:
Find the first four terms of a geometric sequence in which a1 = 5 and r = -3. _____ , _____ , _____ , _____. Find the missing term in the geometric sequence: -7, _______ , -28, 56, _______ , 5 -15 45 -135 × -3 × -3 × -3 14 -112 × -2 × -2 56 ÷ -28 = -2 So, r = -2

Investigation 2: The explicit formula used to find the nth term of a geometric sequence with the first term a1 and the common ratio r is given by: an = a1∙ rn-1 Write a rule for the nth term of the sequence given. Then find a10. , -324, 108, -36, … Rule: an = 972∙(-⅓)n-1 a10 = 972∙(-⅓)10-1 = ____

1, 6, 36, 216, 1296, … Rule: an = 1∙6n-1 a10 = 1∙610-1 =  16. 14, 28, 56, 112, … Rule: an = 14∙2n-1 a10 = 14∙210-1 = 7168

Check for Understanding:
If a5 = 324 and r = -3, write the explicit formula for the geometric sequence and find a10. _____ , _____ , _____ , _____, 324 Rule: an = 4∙(-3)n-1 a10 = 4∙(-3)10-1 = 4 -12 36 -108 OR ÷ -3 ÷ -3 ÷ -3 ÷ -3

If a3 = 18 and r = 3 write the explicit formula for
the geometric sequence and find a10. Rule: an = 2∙(3)n-1 a10 = 2∙(3)10-1 = 39366

If a3 = 56 and a6 = 448 complete the following for
the geometric sequence: _____, _____, 56, _____, _____, 448 14 28 112 224 × 2 ÷ 2 ÷ 2 × 2

20. If r = 2 and a1 = 1 for a geometric sequence,
Write a rule for the nth term of the sequence. b. Graph the first five terms of the sequence. (1, 1), (2, 2), (3, 4), (4, 8), (5, 16) What kind of graph does this represent? exponential

Investigation 3: Sum of a Finite Geometric Series: The sum of the first n terms of a finite geometric series with the common ratio r ≠ 1 is:

Using the formula above, find the indicated sum.
21. a1 = 3, r = 4, n = 13 22. a1 = 7, r = -5, n = 11

Download ppt "Warm Up Section 3.6B (1). Show that f(x) = 3x + 5 and g(x) ="

Similar presentations